Rural Income Generating Activities: Whatever Happened to the Institutional Vacuum? Evidence from Ghana, Guatemala, Nicaragua and Vietnam - Zezza, Alberto; Carletto, Gero; Davis, Benjamin; Stamoulis, Kostas; Winters, Paul (2012)
This paper assesses the current rural development practice against the main trends in recent rural development thinking, based on evidence from four country case studies. While much progress has been made in understanding the need to look beyond only agriculture for the promotion of productive activities in rural areas, and the "institutional vacuum" consistently identified in the rural non-farm (RNF) literature is gradually being filled, much remains to be done. One aspect on which more research is particularly needed is the development of better mechanisms to promote productive investment rather than just social investment and to assess the appropriate level--community, regional, and national--at which to do this.